Coronavirus Disease Knowledge and Attitudes of Nursing Students: A Cross-Sectional Study in Saudi Arabia - Ahmed Abdalla Jarelnape (Sudan Journal of Medical Sciences)
Background: The prevalence of coronavirus disease is increasing rapidly all over the world therefore, this study aimed to understand the knowledge and attitudes among the nursing students about the coronavirus disease. Methods: The design of our study was cross-sectional in the period from January to March, 2020. A survey was conducted by Survey Monkey, the questionnaire link had been shared with the students, according to the inclusion criteria (nursing students in the third and fourth year), the questionnaire included two parts: (i) demographic characteristics of the students and (ii) knowledge and attitudes regarding the coronavirus disease. The number of participants in the study, who completed the questionnaire, was 350. Results: The findings revealed that the average score for their knowledge is good, (13/17 points) reaching 79%. Total 77% students showed a negative attitude about the coronavirus disease and 79.7% students used the website of Ministry of Health for medical information. Conclusion: This study showed that nursing students had a good knowledge about the coronavirus disease and a negative attitude. The Ministry of Health website was instrumental in imparting knowledge to the students about coronavirus.